Perbedaan Sosial dalam Dongeng the Country Mouse and The City Mouse Karya Predeaux - Saepudin Abdulrohman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Human nature, social life, requires humans to socialize with and interact with other humans for survival. There are the five important elements of socialization: social, cultural, social institutions, social stratification or the final grouping of society: power and authority. The study was done to identify social differences and factors that contributed to social differences. The study used qualitative descriptive methods with an objective approach to literature. Well-illustrated social differences in the background of both mice (country mouse) and (city mouse), they had conflicting backgrounds. The cause of these differences is that they live in different neighborhoods.